Good Corporate Governance, Profitability, and Tax Avoidanc - Ni Gusti Ayu Putu Diah Sasmita (E-Jurnal Akuntansi, 2024)
The amount of the tax amnesty for 2016-2017 is evidence of tax evasion by the company. The purpose of this research is to find out how the influence of corporate governance and profitability on tax avoidance. Manufacturing companies in the consumer goods industry that are listed on the Indonesia Stock Exchange in 2020 are the population in this study. Sampling was carried out by purposive sampling technique with a sample of 34 companies. Structural Equation Modeling - Partial Least Square was used as a research data analysis technique. The output of this study reveals that institutional ownership, audit quality and profitability have a negative effect on tax avoidance, but independent commissioners and audit committees have a positive influence on tax avoidance.